قياس مستوى جودة الخدمات الصحية المقدمة في المراكز الصحية في محافظة اللاذقية من وجهة نظر المستفيدين منها (دراسة ميدانية لمركز إشراف الشامية) - محمود حبيب; أسعد باسل أنور (Latakia University Journal - Economic and Legal Sciences Series, 2015)
هدفت هذه الدراسة إلى التعرف على مستوى جودة الخدمات الصحية المقدمة في المراكز الصحية في محافظة اللاذقية , و معرفة مستوى رضى المستفيدين من الخدمات الصحية المقدمة في هذه المراكز، تكون مجتمع الدراسة من العائلات المراجعة للمراكز الصحية في المنطقة المذكورة . استخدم الباحث المنهج الوصفي التحليلي لقياس رضى المستفيدين من جودة الخدمات الصحية المقدمة في المراكز المذكورة، وتم تصميم وتوزيع استبانة على العائلات المستفيدة من الخدمات الصحية المقدمة بغية قياس درجة جودة الخدمات في المراكز المذكورة، كما تم دراسة و تحليل البيانات باستخدام برنامج spss ، و بعد تحليل البيانات تبين عدم توفر جودة للخدمات الصحية المقدمة في المراكز الصحية في منطقة إشراف الشامية وفقا لأبعاد جودة الخدمات الصحية (الملموسية، الاعتمادية، الاستجابة ،التعاطف ،الثقة والأمان) من وجهة نظر المستفيدين من الخدمات المقدمة. This study aimed to identify the level of quality of health services provided in health centers in the province of Lattakia (supervision area of al-Shamia). It also determined the level of satisfaction of beneficiaries on health services provided in these centers. The study community consisted of families who went repeatedly to the health centers in the area. The researcher has used the descriptive analytical method to measure the satisfaction of the beneficiaries with the quality of health services provided in the centers. A questionnaire has been designed and distributed among the beneficiaries families in order to measure the quality level of health services in the centers. Data has been also studied and analyzed by using the SPSS program. After analysis of the data, there was clearly lack of quality of health services provided in health centers al-Shamia ​​supervision area, according to the dimensions of quality of health services (tangibility, reliability, power of responsiveness, empathy, trust and safety) from the viewpoint of the beneficiaries of the services provided.